The effect of torsional shoe sole stiffness on knee moment and gross efficiency in cycling - Fletcher, J. R.; Asmussen, M. J.; Nigg, S. R.; MacIntosh, B. R.; Nigg, B. M. (Journal of Sports Sciences, 2019)
Altering torsional stiffness of cycling shoe soles may be a novel approach to reducing knee joint moments and overuse injuries during cycling. We set out to determine if the magnitude of three-dimensional knee moments were different between cycling shoe soles with different torsional stiffnesses. Eight trained male cyclists cycled at 90% lactate threshold power output in one of two cycling shoe conditions in a randomized crossover design. The shoe sole was considered torsionally flexible (FLEX) compared to a relatively stiffer (STIFF) sole. Gross efficiency (GE) and knee joint moments were quantified. No significant effect of shoe condition was seen in GE (21.4 ± 1.1% and 20.9 ± 1.6% for FLEX and STIFF, respectively, P = 0.12), nor in three-dimensional knee moments. 4 of the 8 subjects had reduced knee moments in at least 2 of the 3 moment directions. These "responders" were significantly shorter (1.73 ± 0.02 m vs 1.81 ± 0.04 m, P = 0.017) and had a higher relative maximal aerobic power (MAP) (4.6 ± 0.3 W·kg-1 vs 3.9 ± 0.3 W·kg-1, P = 0.024) compared to non-responders. These results suggest that certain shoe characteristics may influence certain individuals differently because these participants belong to different "functional groups"; certain individuals may respond positively to FLEX, while others may not. Further studies should test this proposed hypothesis.